The Implementation of Covid-19 Archives Preservation in College - Lolytasari Lolytasari; Hikmah Irfaniah (Record and Library Journal, 2022)
Background of the study: Circular Letter No. 62 of 2020 concerning the Preservation of Covid-19 handling archives is a public policy that needs to be implemented by State Universities as part of government agencies.